Sosialisasi Materi Public Speaking untuk Pengurus OSIS di SMP Negeri 2 Sangatta Utara - Eko Nursalim; Aham Mutasyarifin; Muhammad Yoga Julyanur; Ratih Fatonah; Thayyibatul Islamiyah; Safitri Safitri; Ramlah Harniati Hapsah (ARDHI : Jurnal Pengabdian Dalam Negri, 2024)
Community Service (PkM) activities through socialization of public speaking materials for student council administrators at SMP Negeri 2 Sangatta Utara aims to improve the verbal communication skills and self-confidence of the participants. This training includes the provision of material on basic public speaking techniques, the use of body language, and emotional control, which is carried out through presentations, discussions, and question and answer sessions. The results of this activity showed an increase in understanding and public speaking skills among participants, which was reflected in their enthusiasm in following each stage of the activity. In addition, this socialization also provided an opportunity for participants to hone their leadership skills and communicate effectively in the school environment. Recommendations for future activities include organizing more interactive training with hands-on practice, in order to achieve more optimal results. Thus, this activity is expected to be an inspiration for similar PkM programs in the future, which aim to develop important skills for the younger generation.)